The problem of reduction of geometry and graphic training departments in Russian universities - S. I. Rotkov; E. V. Konopatskiy; K. L. Panchuk (Омский научный вестник)
In the article the authors raised the problem of reduction of geometry-graphic training departments in Russian universities, which for the last 16 years amounted to about 1/3. The reasons for this situation are considered, among which should be emphasized the lack of highly qualified personnel of higher qualification, capable of leading scientific schools in the profile of geometric-graphic training departments. It is proposed to activate the work of the departments of geometry-graphic training on training of scientific-pedagogical staff of higher qualification in postgraduate and doctoral studies. It is also proposed to fix for engineering specialties at the level of the state standard the necessary labor intensity and more stringent requirements to the staff conditions for the implementation of the basic professional educational program with regard to the disciplines of geometric-graphic training of students.